Research Misconduct and Its Determinants in Accounting Research Environment - Mohammad Hossein Safarzadeh (Shahid Bahonar University of Kerman, 2016)
Misconducting research tarnishes the reputation and credibility of research institutions. This study examines the attitudes and perceptions in a group of accounting researchers about misconduct research and its determinants or related factors in the Iranian accounting research environment. To collect the data needed for the study, we prepared an adapted scientific misconduct questionnaire, and then, asked for answers from the accounting researches. First, a descriptive analysis of the answers was performed, using data frequencies of the answers. Then, Likert scale responses were transformed into dichotomous answers. At the end, one sample sign test was performed to analyse the research questions. The results showed that the Iranian group of accounting researchers perceive that scientific misconduct is commonplace in their accounting research environment, and that they are concerned about the negative effects of scientific misconduct on the credibility of scientific research. It is recommended that researchers should be empowered with the knowledge and virtues required for self-regulation that advance research integrity. Also, research institutes should take steps towards regulating the current state and fostering responsibility for research ethics to discourage misconduct.